Mulheres negras e professoras no ensino superior: as histórias de vida que as constituíram - Reis, Maria Clareth Gonçalves (2009)
This work has as principal aim to understand the process of race identity construction of black university teachers. As specifics aims, I tried to perceive how the process of race, gender and class identity construction are lived for the teachers and to understand their perceptions about blackness and social classes that they are included. For this, I used a qualitative approach, choosing the oral history because this approach it is the best for the aims proposed. To produce the data, I used life stories interviews, considering the teacher s trajectories. The choice of these teachers was guided by qualitative criteria, emphasizing the meaning of their individual and collectives experiences. I did five interviews, according with the profile previously settled, it means, university teachers that had declared herselves as black women. The choice of this number of interviews was also orientated by qualitative criteria, considering the choice of oral history. This study was divided in four chapters; in the first one, I show the incitements, the challenges and the aspirations that bring me to the discussion of this theme, the contextualization of these study and its methodological options. In the second chapter, I focus in the construction process of black identities connected with gender identities, besides the conceptual discussion of gender, stigma, stereotype, race, racism, etc. In the third chapter, I present the racism lived by the teachers into school and familiar environment; their perceptions about the pedagogical optimism and the references that interfering in the constitution of their racial, gender and class identities. In the last chapter, I emphasized the interconnections between the identities discussed; the tensions about the black middle-class; the inequalities of black population to the access and permanence in the university teaching; the courses where the black women are; their participation in the racial discussion as teachers. Finally, I show the ambiguities and the conflict related with the black identities construction lived by these teachers, that are repeated in their families. Both of them point out to the importance of memories, the rescue to the ancestor s stories in the son s and daughter s identity construction. I perceive, in this study, that the dichotomy race and class still need to be discussed, because a lot of people go on asserted that the black people problem it is reduced to the class question and another to the race matter. The teachers interviewed showed that, a lot of times, racial condition overlaps class condition. The discriminations pointed out difficult the social, economic and cultural ascension of black women and when they ascend are perceived like been out of place .